Congenital syphilis present with pemphigus syphilitics and atelectatic congenital pneumonia: a case report - Callista Beatrice; Indriana Triastuti; I Gde Doddy Kurnia Indrawan (Intisari Sains Medis, 2021)
Background: Congenital syphilis is an infectious disease of newborns caused by Treponema pallidum, a spirochete bacterium, from vertical transmission from infected mother to fetus. Diagnosis of congenital syphilis can be difficult because two-thirds of affected infants are asymptomatic at birth, and the signs of symptomatic infants are diverse. Familiarity with the various presentations is essential to early diagnosis and treatment.Case Description: A male preterm, 35 weeks gestation baby, born by vaginal delivery from G1P0 mother with syphilis latent phase, with Treponema pallidum hemagglutination assay (TPHA) titer reactive (1:2560) with no treatment during the antenatal period. The baby was born with low birth weight, respiratory distress syndrome, hepatosplenomegaly, and skin rash.  Diffuse desquamation and fissures also multiple eroded pale blisters are known as pemphigus syphilitics. TPHA was also reactive at the same level as the mother. Complete blood count showed severe respiratory acidosis (pH: 6,8), leucocytosis (46.420/uL), thrombocytosis (414.000/uL), lymphocytosis (40,3%), and monocytosis (16%). Radiology showed severe atelectatic left lung and course nodular congenital pneumonia of the right lung. The baby was intubated and injected with penicillin procaine 50.000 IU/kg/day intramuscularly in the neonatal intensive care unit (NICU). However, due to severe atelectatic lung and acidosis, this case resulted in a fatal outcome.Conclusion: Broad desquamation, multiple fissures, and eroded pale blisters (vesiculobullous lesions) known as pemphigus syphilitics should alert clinicians as an early manifestation of congenital syphilis. Other manifestations include congenital pneumonia, typically atelectatic or nodular type, and hepatosplenomegaly. Treatment should be started promptly to decrease its morbidity and mortality.